Hockney's eye the art and technology of depiction - Gayford, Martin 1952-; Kemp, Martin 1942-; Munro, Jane 1958- (Paul Holberton Publishing, 2022)
Throughout his long career, David Hockney has insistently explored diverse ways of depicting the visible world. He has scrutinised the methods of the old masters, and explored radical departures from their cherished assumptions. The exhibitions accompanied by this volume are the first to focus on this central theme in his art. 'Western art' from the Renaissance until at least the late 19th century has been dominated by the depiction of nature. Was this to be accomplished by direct looking (called "eyeballing" by Hockney) or with the assistance of optical theory and devices, such as cameras? Hockney has experimented with the full range of existing strategies, overtly using perspective in some of his classic pictures and rigorously investigating optical aids for the imitation of nature, including the camera obscura and camera lucida. Yet he has come to reject the photograph as the definitive image of what we see.
Rückseite Titelblatt: First published to accompany the exhibition "Hockney's Eye: the Art and Technology of Depiction", The Fitzwilliam Museum, Cambridge, 15 March - 29 August 2022; The Heong Gallery, Cambridge, 15 March - 29 August 2022; Teylers Museum, Haarlem, 24 September 2022 - 30 January 2023
Keywords: Hockney, David -- 1937-; Optisches Instrument; Perspektive; Maltechnik; Hockney, David / Exhibitions; Art and technology / Exhibitions; Hockney, David; Exhibition catalogs; Ausstellungskatalog -- Fitzwilliam Museum -- 15.03.2022-29.08.2022 -- Cambridge; Ausstellungskatalog -- The Heong Gallery -- 15.03.2022-29.08.2022 -- Cambridge; Ausstellungskatalog -- Teylers Museum -- 24.09.2022-30.01.2022 -- Haarlem